Analysis on effect of lateral straggle on analog, high frequency and DC parameters in Ge‐source DMDG TFET. Issue 4 (9th February 2021) - Saha, Rajesh; Panda, Deepak Kumar; Goswami, Rupam; Bhowmick, Brinda; Baishya, Srimanta
Abstract: The diffusion of doping concentration in source/drain regions through ion implantation technique extents to the channel, which decreases the inversion portion of channel and results in variation of device behavior. In this paper, by merging the advantages of Ge‐source TFET and dual material gate (DMG) TFET, a new device named as Ge‐source dual material double gate (DMDG) TFET is proposed. We have investigated DC parameters like drain current vs gate bias, drain current vs drain bias, subthreshold swing (SS), and current ratio ( I ON / I OFF ) by changing the lateral straggle parameter ( σ ) from 0 to 5 nm through TCAD device simulator in proposed TFET. The RF/analog behavior like transconductance ( g m ), output conductance ( g d ), intrinsic gain ( g m / g d ), total gate capacitance ( C gg ), cut‐off frequency ( f c ), transconductance generation factor (TGF), transconductance frequency product (TFP), gain frequency product (GFP), and gain transconductance frequency product (GTFP) are reported for different σ values in proposed TFET. It is found that both DC and RF/analog figure of merits are a function of σ . It is perceived that I ON as well as RF/analog characteristics are improved, whereas, short channel parameter degrades with increase in σ . Finally, the effect of σ on noise performance and s‐parameters are highlighted in proposed device.